Mesoporous carbon/graphitic carbon nitride spheres for photocatalytic H2 evolution under solar light irradiation. (18th March 2020) - Baca, M.; Dworczak, M.; Aleksandrzak, M.; Mijowska, E.; Kaleńczuk, R.J.; Zielińska, B.
Abstract: Herein, two different photocatalytic composites based on ordered (OCS) and disordered (DCS) mesoporous hollow carbon spheres and graphitic carbon nitride (gCN) have been successfully fabricated through facile acid treatment. The influence of carbon shell morphology of the spheres on gCN loading and photocatalytic H2 production under simulated solar light irradiation has been revealed. The amount of evolved H2 was 6.2 (OCS/gCN) and 5.3 (DCS/gCN) times higher in comparison to pristine gCN. It was found that graphitic carbon nitride was much more homogenously supported onto ordered mesoporous carbon spheres than disordered ones. The deposition of gCN onto ordered carbon spheres was found to be more efficient to increase carrier concentration, enhance photogenerated charge carrier transport and separation. It is assigned to the formation of the graphitic carbon nitride/carbon heterojunction facilitating the contact surface between the two phases of hybrid. Therefore, via tuning of the morphology of carbon shell being a host for gCN it was possible to find more promising candidate as a photocatalyst in H2 production under solar light irradiation. Graphical abstract: Image 1 Highlights: Graphitic carbon nitride was deposited onto mesoporous hollow carbon spheres. Hybrids displayed enhanced H2 production in respect to the pristine carbon nitride. The effect of carbon shell morphology on photocatalytic abilities was studied. The electrochemical behavior of the most efficient catalyst was examined.